Isolation, structure elucidation and quantitative analysis of callicarpone and oleanolic acid in the leaves of Callicarpa candicans collected from different provinces in Thailand - Muensaen, Sarinthip; Ruangwises, Nongluck; Jarikasem, Siripen; Sithisarn, Pongtip (Agriculture and Natural Resources, 2019)
Callicarpa candicans (‘khi-on-don’ in Thai) is a plant that has been traditionally recognized for its potential use as a piscicidal agent. Two major compounds were separated from the dichloromethane extract from the leaves of C. candicans using solvent-solvent extraction and a column chromatographic technique. These compounds were structurally identified using spectroscopic techniques as callicarpone and oleanolic acid. Quantitative analysis of callicarpone and oleanolic acid using high performance liquid chromatography (HPLC) was developed and validated. The callicarpone and oleanolic acid contents in C. candicans leaves collected from different provinces in Thailand were analyzed using the validated HPLC method. The callicarpone and oleanolic acid contents in C. candicans leaves were in the ranges 0.04–0.23 g% and 0.44–0.88 g% of dried leaves, respectively. The leaves of C. candicans collected from Satun province had the highest callicarpone and oleanolic acid contents (0.23 g% and 0.88 g% of dried leaves, respectively). The HPLC analytical method using callicarpone and oleanolic acid as markers could be used for future standardization and quality control of the extract of C. candicans leaves.